Compósito de poliuretano elastomérico reforçado com fibra de juta: estudo das propriedades dinâmico-mecânicas e viscoelásticas - Oliveira, Robson Morijo de (Universidade Federal de São Carlos, 2013)
Composite technology of a polymer matrix reinforced with artificial fibers, like fiberglass, Kevlar, carbon, etc., has become specialty in recent times moved by advances in technology in some sectors such as automotive and aerospace. The composites already have come a long way in replacing conventional materials like metals and Woods. However with the goal to reduce costs and provide a sustainable growth, science has directed his attention in reinforced compounds with renewable material such as natural fibers. In this work, a study was conducted of the dynamic behavior-mechanical and thermodynamic transitions of second order, as is the case of the glass transition temperature, matrix composite polyurethane elastomers with jute fiber reinforcement. The relaxation that occurs in glassy transition region, also called primary relaxation or relaxation α to amorphous polymers, molecular movements resulting from long distances, involving the main polymer chain segments. The matrix was formed by a MDI-BDO system provided by the company Metso Brazil, PU Division. Metso Brazil manufactures PU screens used in crushing sieves in the mining industry, and this work studied replacing the pure PU fiber by composite reinforced with jute. The material was prepared in an open heated to 100º C with controlled temperature, the system was synthesized in a mixer pre-polymer ratio automatic PU of Baulé on following conditions: MDI, 45º C to 9.5 bar; BDO, 45 C 5.7 bar and D20, 69 C a11 .2 bar. For the characterization of mechanical properties of composite dynamic-mechanical analysis was performed in tension in a temperature range of 35 to 160° C and bending creep. The results showed that the composite had formed showed lower creep deformation in bending test compared to pure polyurethane, but higher strain compared to the composite fiberglass. The flexural modulus (E ') of jute fiber composite showed a higher value at higher temperatures than the unreinforced material. The composi
COMPOSITE OF ELASTOMERIC POLYURETHANE MATRIX REINFORCED WITH SUPERFICIALITY MODIFIED JUTE FIBER: STUDY VISCOELASTIC PROPERTIES AND INTERFACIAL ADHESION.
Keywords: materiais compósitos; materiais viscoelásticos; poliuretano; compósito; fibra de juta, análise dinâmico-mecânica; polyurethane; composite; jute fiber; dynamic-mechanical analysis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES